High doses of dexamethasone induce increased beta-cell proliferation in pancreatic rat islets - Rafacho, Alex; Cestari, Tania M.; Taboga, Sebastiao R. [UNESP]; Boschero, Antonio C.; Bosqueiro, Jose R. [UNESP] (Amer Physiological Soc, 2009)
Rafacho A, Cestari TM, Taboga SR, Boschero AC, Bosqueiro JR. High doses of dexamethasone induce increased beta-cell proliferation in pancreatic rat islets. Am J Physiol Endocrinol Metab 296: E681-E689, 2009. First published January 21, 2009; doi:10.1152/ajpendo.90931.2008.-Activation of insulin signaling and cell cycle intermediates is required for adult beta-cell proliferation. Here, we report a model to study beta-cell proliferation in living rats by administering three different doses of dexamethasone (0.1, 0.5, and 1.0 mg/kg ip, DEX 0.1, DEX 0.5, and DEX 1.0, respectively) for 5 days. Insulin sensitivity, insulin secretion, and histomorphometric data were investigated. Western blotting was used to analyze the levels of proteins related to the control of beta-cell growth. DEX 1.0 rats, which present moderate hyperglycemia and marked hyperinsulinemia, exhibited a 5.1-fold increase in beta-cell proliferation and an increase (17%) in beta-cell size, with significant increase in beta-cell mass, compared with control rats. The hyperinsulinemic but euglycemic DEX 0.5 rats also showed a significant 3.6-fold increase in beta-cell proliferation. However, DEX 0.1 rats, which exhibited the lowest degree of insulin resistance, compensate for insulin demand by improving only islet function. Activation of the insulin receptor substrate 2/phosphatidylinositol 3-kinase/serine-threoninekinase/ribosomalprotein S6 kinase pathway, as well as protein retinoblastoma in islets from DEX 1.0 and DEX 0.5, but not in DEX 0.1, rats was also observed. Therefore, increasing doses of dexamethasone induce three different degrees of insulin requirement in living rats, serving as a model to investigate compensatory beta-cell alterations. Augmented beta-cell mass involves beta-cell hyperplasia and, to a lower extent, beta-cell hypertrophy. We suggest that alterations in circulating insulin and, to a lesser extent, glucose levels could be the major stimuli for beta-cell proliferation in the dexamethasone-induced insulin resistance.
Keywords: beta-cell growth; glucocorticoid; hyperglycemia; hyperinsulinemia; insulin resistance